2016
DOI: 10.1177/1369148116668079
|View full text |Cite
|
Sign up to set email alerts
|

Exploring sex differences in attitudes towards the descriptive and substantive representation of women

Abstract: Academic discussions about the political (under-)representation of women tend to focus on descriptive or substantive representationthat is, the numbers of women present in politics or the representation of so-called 'women's interests' in politics. As such, arguments in favour of increases in women's representation tend to invoke either or both of these ideas. Many, for example, argue that an increase in the descriptive representation of women (DRW) may result in an equivalent, or related, increased in the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…Electing more women can lead to greater government investment in issues seen as particularly relevant to gender equality (Bolzendahl 2011; Celis 2006; Cowell-Meyers and Langbein 2009; Schwindt-Bayer and Mishler 2005; Wängnerud 2009), suggesting that substantive representation is at play. Public opinion research in Northern Ireland also found support for the belief that increasing women's descriptive representation would improve the representation of women's interests, and this effect was particularly strong for women (Allen and Cutts 2016). A British public opinion study revealed that respondents tended to disagree that women can better represent ‘women's interests’ than men, though women, more than men, were more inclined to believe that women could (Campbell and Heath 2017).…”
Section: Crafting Support For Greater Formal and Informal Equality Inmentioning
confidence: 95%
“…Electing more women can lead to greater government investment in issues seen as particularly relevant to gender equality (Bolzendahl 2011; Celis 2006; Cowell-Meyers and Langbein 2009; Schwindt-Bayer and Mishler 2005; Wängnerud 2009), suggesting that substantive representation is at play. Public opinion research in Northern Ireland also found support for the belief that increasing women's descriptive representation would improve the representation of women's interests, and this effect was particularly strong for women (Allen and Cutts 2016). A British public opinion study revealed that respondents tended to disagree that women can better represent ‘women's interests’ than men, though women, more than men, were more inclined to believe that women could (Campbell and Heath 2017).…”
Section: Crafting Support For Greater Formal and Informal Equality Inmentioning
confidence: 95%
“…Yet, the main literature on citizen support for gender quotas, and more broadly women in politics, do not explore whether citizens might support gender quotas for patronizing, or potentially sexist, reasons (but see Pereira & Porto, 2020). Previous investigations emphasize attitudes toward gender equality (Beauregard, 2018; Gidengil, 1996; Keenan & McElroy, 2017), support for government involvement (Barnes & Córdova, 2016), partisanship and ideology (Dubrow, 2011), elite cues (Morgan & Buice, 2013), or a desire for descriptive and substantive representation (Allen & Cutts, 2016; Bolzendahl & Coffé, 2020) as explanations for quota support. We further explore a crucial set of explanations for understanding gender‐quotas support that nuances the previous understanding that greater commitment toward gender equality should be linked with greater support.…”
Section: Ambivalent Sexism and Affirmative Actionmentioning
confidence: 99%
“…Research has mostly focused on explaining support for legislative quotas (Barnes & Córdova, 2016; Beauregard, 2018; Dubrow, 2011; Gidengil, 1996; Keenan & McElroy, 2017; Pereira & Porto, 2020)—that is, policies promoting constitutional or legislative change to mandate and require political parties to designate a certain percentage of women candidates for election (Krook et al, 2009). Respondents appear more likely to support these policies if they themselves are a potential beneficiary (Bolzendahl & Coffé, 2020), if they have a preexisting commitment to equality (Gidengil, 1996), if they believe that government should be involved to decrease inequalities (Barnes & Córdova, 2016), if they agree that the presence of women provide symbolic benefits (Bolzendahl & Coffé, 2020), or if they want women to have greater substantive representation (Allen & Cutts, 2016). Haley and Sidanius (2006) argue that individuals' response to affirmative action is conditioned both by “prepackaged” conceptualizations of the issue and their existing predilections.…”
Section: Ambivalent Sexism and Affirmative Actionmentioning
confidence: 99%
“…Support for more descriptive representatives of a particular group is likely to depend on support for those policies the descriptive representatives are likely to advocate (Allen & Cutts 2016; Casellas & Wallace 2015; Dolan & Sanbonmatsu 2009). Given the greater likelihood of Republican identification among white women compared with WOC, and the fact that more women in Congress are Democrats, respondent party identification should play a role in support for greater descriptive representation of WOC.…”
Section: Analysis: Understanding Women’s Support For Woc In Elective Officementioning
confidence: 99%